1999
DOI: 10.1007/s001470050254
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary liver transplantation: how to improve regeneration of the native liver by surgery

Abstract: The technical factors which could influence regeneration of the native liver (NL) in auxiliary liver transplantation (ALT) for fulminant hepatic failure (FHF) are not well known. We studied NL regeneration according to the location of graft anastomosis in the recipient's portal system (superior mesenteric vein versus portal vein), and graft weight (50 ' 740 reduced-size versus full-size graft) in a rat model of ALT with 80 % reduction of the NL, and graft arterialization. NL regeneration was significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The implanted liver was able to maintain normal liver function ( 15 ). The total weight of the donor and the recipient livers was significantly higher compared to the weight of standard liver required by the recipient, which was similar to the findings of Sauvanet et al ( 14 ). However, other studies ( 11 , 16 ) demonstrated that the total weight of the liver required by the recipients following transplantation was regulated by body weight and the final ratio of liver weight to body weight was constant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The implanted liver was able to maintain normal liver function ( 15 ). The total weight of the donor and the recipient livers was significantly higher compared to the weight of standard liver required by the recipient, which was similar to the findings of Sauvanet et al ( 14 ). However, other studies ( 11 , 16 ) demonstrated that the total weight of the liver required by the recipients following transplantation was regulated by body weight and the final ratio of liver weight to body weight was constant.…”
Section: Discussionsupporting
confidence: 89%
“…Sauvanet et al ( 14 ) reported that a whole or half transplanted liver to an ectopic site may promote regeneration of the host liver in their established rat model following acute liver failure induced by 80% liver resection treated by auxiliary liver transplantation. Even with the same surgical procedure, whole-liver transplants may more effectively promote the regeneration of the host liver in the short term compared to partial liver transplants.…”
Section: Discussionmentioning
confidence: 99%